Evolution of TERT-interacting lncRNAs: expanding the regulatory landscape of telomerase - Nelson, Andrew D.; Shippen, Dorothy (Frontiers in Genetics, 2015)
Long noncoding RNAs (lncRNAs) evolve rapidly and are functionally diverse. The emergence of new lncRNAs is driven by genome disturbance events, including whole genome duplication, and transposition. One of the few lncRNAs with a conserved role throughout eukaryotes is the telomerase RNA, TER. TER works in concert with the telomerase reverse transcriptase (TERT) to maintain telomeres. Here we discuss recent findings from Arabidopsis thaliana and its relatives illustrating the remarkable evolutionary flexibility within TER and the potential for non-canonical TERT-lncRNA interactions. We highlight the two TERs in A. thaliana. One is a conventional telomerase template. The other lncRNA negatively regulates telomerase activity in response to DNA damage, a function mediated by co-option of a transposable element. In addition, we discuss evidence for multiple independent TER loci throughout the plant family Brassicaceae, and how these loci not only reflect rapid convergent evolution, but also the flexibility of having a lncRNA at the core of telomerase. Lastly, we discuss the propensity for TERT to bind a suite of non-templating lncRNAs, and how such RNAs may facilitate telomerase regulation and off-telomere functions.